Analysis of Renewable Energy Potential In The Implementation of NZE 2060 To Support Defence In Indonesia - Rheviany HS Putri; Panji Suwarno; Lukman Yudho Prakoso; Inez Koerniawati; Tri Yulianto; Nur Khotimah (PT. Publikasiku Academic Solution, 2023)
This paper discusses changes in environmental quality caused by the increase in the earth’s temperature which is increasing every year. The impact of rising earth temperature includes environmental damage, economic losses, and social losses. Therefore, several countries have discussed renewable energy as a solution to withstand the increase in earth’s temperature, one of which is through the concept of NZE (Net Zero Energy) which aims to reduce dependence on fossil energy sources. The implementation of NZE in Indonesia in 2060 is expected to support the national Net Zero Emission (NZE) 2060 program, which is a continuation of the follow-up to the Paris Agreement. In addition, the author also relates government support in order to maximize the potential of Renewable Energy in the Application of NZE can also support the defense of the Indonesian state. The research method used is a qualitative method in the form of an objective narrative literature review.